Ordartikkelen i nokre norske ordbøker i historisk perspektiv - Worren, Dagfinn (Nordiske Studier i Leksikografi, 2003)
This article deals with the information categories in the entries of some Norwegian dictionaries from a historical perspective. Ivar Aasen’s Ordbog over det norske Folkesprog (Dictionary of the Norwegian Dialects) from 1850 is the first modern dictionary of Norwegian, also in terms of information categories. This dictionary uses all of the five classical information types: formal, semantic, combinatory, encyclopaedic, and historical. The very first Norwegian dictionary in this tradition, which is from 1646, demonstrates only the basic categories (the formal, the semantic, and the combinatory ones). However, the comprehensive and documentary dictionaries of our time still use the same information categories as Aasen’s dictionary of 1850, though with more subtle and allincluding portraits for each entry. The linguistic description seems to be complete. Consequently, new developments in information types are likely to occur in the encyclopaedic category by means of information technology.